Irregularity Invariants for Chemical Structures Used in the Treatment of COVID-19 - Abaid ur Rehman Virk; Shams Bilal; Khalid Hamid (Scientific Inquiry and Review, 2020)
The world is going through the pandemic of COVID-19. Remdesivir, chloroquine, hydroxychloroquine and theaflavin are some drugs currently in use for the treatment of the COVID-19 patients. This manuscript aims to compute the irregularity measures for these chemical structures. We believe that our results can be utilized to improve the capacity of these chemical structures.Copyright(c) The Authors